The Tomb of Mereruka: a document on his life and character - Kanawati, Naguib (Buried History: The Journal of the Australian Institute of Archaeology, 2008)
A purely metaphoric/symbolic interpretation of the depictions in Old Kingdom tombs is questionable considering the specific events and practices that are often depicted. In particular the decoration in the Tomb of Mereruka provides an understanding of the life and character of the tomb-owner who is seen to be a man of power and wealth. His emphasis on security seems to have contributed to the growth of violence in ancient Egypt.